IMPLEMENTASI ASURANSI USAHA TANI PADI SEBAGAI PERLINDUNGAN HUKUM BAGI PETANI DI KABUPATEN KARAWANG AKIBAT BENCANA BANJIR - Erdin Tahir; Tri Setiady; Meita Fadhilah (Yustitia, 2025)
This study aims to examine the implementation of the Rice Farming Insurance Programme (AUTP) in Karawang Regency as part of the legal protection provided by the government. Karawang Regency is known as a rice-producing area and a national granary that has significantly contributed to the national rice supply. However, geographically, Karawang Regency is relatively low-lying and susceptible to flooding, where a portion of the rice fields experiences inundation during the rainy season, resulting in crop failure (puso). Consequently, the AUTP programme is highly beneficial for farmers in managing risks and losses. This research employs an empirical normative legal methodology, focusing on the analysis of legal norms as well as their application and implementation. The findings indicate that the AUTP programme in Karawang Regency serves as legal protection for farmers against the risks of crop failure due to flood disasters. From 2020 to 2024, the local government allocated a budget of IDR 3.203.843.040 for the AUTP programme, with claims made for 1.914,96 hectares and a total indemnity paid amounting to IDR 11.492.160.000. Furthermore, in 2024, the local government of Karawang Regency allocated IDR 1.440.000.000 in the regional budget for 40.000 hectares of rice fields within the AUTP programme. Keywords: Crop failure; Floods; Insurance; Legal Protection.